2017
DOI: 10.1080/03639045.2017.1386209
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-alcoholic media effects on theophylline release from sesamum polysaccharide gum matrices

Abstract: Concomitant ingestion of alcohol and medications can greatly affect drug plasma concentrations as dose dumping or failure may occur as a result of the fact that formulation excipients may not always be resistant to alcohol. In this study, a natural polysaccharide (Sesamum radiatum gum) (SG) was extracted, characterized and used to formulate sustained release theophylline compacts to study the effect of varying alcohol concentrations (v/v) in dissolution media on drug release from these compacts. X-ray powder d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The other event on the sesamum DSC trace is attributed to the polysaccharide decomposition (Zohuriaan and Shokrolahi 2004;Varma et al, 1997) between 251 and 302.3 °C. This phenomenon was confirmed using TGA analysis as a final weight loss of ~ 54.6 % by Nep et al 2018 with the thermal scission of carboxylate or carboxylic acid groups resulting in the evolution of C02 from the corresponding carbohydrate backbone being a probable mechanism for the observations. Figure 3c highlights that the characteristic peaks of PPN was present in all formulations (conventional and liquisolid).…”
Section: Solid-state Analysis Of Starting Materials and Formulationsmentioning
confidence: 59%
See 2 more Smart Citations
“…The other event on the sesamum DSC trace is attributed to the polysaccharide decomposition (Zohuriaan and Shokrolahi 2004;Varma et al, 1997) between 251 and 302.3 °C. This phenomenon was confirmed using TGA analysis as a final weight loss of ~ 54.6 % by Nep et al 2018 with the thermal scission of carboxylate or carboxylic acid groups resulting in the evolution of C02 from the corresponding carbohydrate backbone being a probable mechanism for the observations. Figure 3c highlights that the characteristic peaks of PPN was present in all formulations (conventional and liquisolid).…”
Section: Solid-state Analysis Of Starting Materials and Formulationsmentioning
confidence: 59%
“…by Nep et al 2018. The authors observed minor weight loss of ~ 11.5 % between -140 °C using TGA analysis and DSC.…”
Section: Solid-state Analysis Of Starting Materials and Formulationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Nep et al also explored starch-free grewia polysaccharide in comparison to the native grewia gum and found extraction of starch to improve the blending process and increase the resistance of the polysaccharides to alcohol damage [ 16 ]. The same authors also explored the effects of hydroalcoholic media on an extracted sesamum gum polysaccharide [ 17 ]. Ethanol has been reported to not have any dose dumping repercussions on the kinetics of drug release from hypromellose incorporated matrices [ 2 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transport across this layer is by diffusion, but erosion can also occur when the polymer chains begin to untangle, as this happens the drug begins to be released [3]. The natural polymers have been used as matrices for sustained release [4][5][6][7][8][9][10][11][12] stabilizers or suspending agents in liquid dosage forms [13] and in bioadhesive drug delivery systems [14,15]. Apart from the fact that the natural materials are biocompatible, they have the additional advantages of being low cost and relatively abundant [16][17][18] compared to their synthetic counterparts.…”
Section: Introductionmentioning
confidence: 99%